The potential of antagonistic bacteria from shrimp paste as inhibitors of spoilage bacteria in fishery products - Sukmawati, Sukmawati; Metusalach, Metusalach; Syahrul, Syahrul; Radjawane, Christy (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
Spoilage bacteria present a considerable obstacle in the preservation of seafood items, including shrimp and fish, leading to economic losses, health hazards, and degradation of product quality. Prevalent spoilage bacteria in seafood comprise Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. This study seeks to assess the inhibitory potential of bacterial isolates obtained from shrimp paste against rotting spoilage bacteria. A descriptive approach was employed to assess the antibacterial activity of four bacterial isolates—designated TRS 1, TRS 2, TRS 3, and TRS 4—against Gram-positive and Gram-negative spoilage bacteria. The inhibitory effect was measured by the diameter of the clear zones surrounding the isolates. The findings indicated that isolate TRS 1 exhibited the most significant inhibition against Staphylococcus aureus (19.0 mm) and Klebsiella pneumoniae (9.5 mm), whereas isolate TRS 4 displayed the greatest inhibition against Escherichia coli (12.0 mm). The findings indicate that some bacterial isolates from shrimp paste exhibit significant antagonistic activity and may function as natural preservatives in seafood products. Additional research is required to validate bacteriocin synthesis by molecular and biochemical techniques and to assess their practical implications in seafood preservation.